Colovesical fistula: a rare complication after renal transplantation. (6th January 2018) - Subbiah, Arunkumar; Mahajan, Sandeep; Yadav, Raj Kanwar; Agarwal, Sanjay Kumar
Abstract : Colovesical fistula per se is a rare condition and most commonly occurs secondary to diverticular disease in normal patients. Colovesical fistula in the setting of post-renal transplantation is even rarer and very few cases have been reported in literature. Patients with autosomal-dominant polycystic kidney disease (ADPKD) are predisposed to diverticulosis and hence are at a higher risk for fistula formation. Herein, we report a case of colovesical fistula in a renal allograft recipient with ADPKD in the absence of diverticulosis. The patient was successfully operated and is stable with no complications at 1-year follow-up.